2013
DOI: 10.2139/ssrn.2214005
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Some Insurers Become Systemically Relevant?

Abstract: Are some insurers relevant for the stability of the financial system? And if yes, what firm fundamentals and aspects of insurers' business models cause them to destabilize an entire financial sector? We find that several insurers did indeed contribute significantly to the instability of the U.S. financial sector during the recent financial crisis. We empirically confirm that insurers that were most exposed to systemic risk were larger, relied more heavily on non-policyholder liabilities and had higher ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Therefore, it has become a first-order priority to understand not only how insurance companies contribute to systemic risk of the overall financial sector but also when and why they have increased their systemic exposure and their systemic contribution. The literature identifies the main drivers of risk in the growth of non-traditional funding and non-traditional investment activities (Cummins and Weiss, 2014; Weiss and Mühlnickel, 2014)[2]. Moreover, insurance companies and banks are becoming more and more interconnected (Cummins and Boettner, 2011; Chen et al , 2013, Billio et al , 2011) as the insurers business models are rapidly changing, and their returns are comoving more with banks returns.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has become a first-order priority to understand not only how insurance companies contribute to systemic risk of the overall financial sector but also when and why they have increased their systemic exposure and their systemic contribution. The literature identifies the main drivers of risk in the growth of non-traditional funding and non-traditional investment activities (Cummins and Weiss, 2014; Weiss and Mühlnickel, 2014)[2]. Moreover, insurance companies and banks are becoming more and more interconnected (Cummins and Boettner, 2011; Chen et al , 2013, Billio et al , 2011) as the insurers business models are rapidly changing, and their returns are comoving more with banks returns.…”
Section: Introductionmentioning
confidence: 99%
“…The latter reference analyzes the ability of the insurance industry to disrupt the financial market. It is indeed observed that insurers may contribute to the instability of the financial sector, especially through their noncore activities, see [7][8][9][10][11]. These observations are based on systemic risk measures that allow for the study of the interconnectedness between insurers and other financial institutions, see [12][13][14].…”
Section: Introductionmentioning
confidence: 99%